Experimental pancreatitis is mediated by low-affinity cholecystokinin receptors that inhibit digestive enzyme secretion. - Saluja, A K (1989)
Rats infused with a supramaximally stimulating dose of the cholecystokinin (CCK) analog caerulein develop acute edematous pancreatitis. Using CCK-JMV-180, a recently developed CCK analog that acts as an agonist at high-affinity CCK receptors but antagonizes the effect of CCK at low-affinity receptors, we have determined that caerulein induces pancreatitis by interacting with low-affinity CCK receptors. Those low-affinity receptors mediate CCK-induced inhibition of digestive enzyme secretion from the pancreas. Our observations, therefore, suggest that this form of experimental pancreatitis results from the inhibition of pancreatic digestive enzyme secretion.